Modeling of Spherical Dust Particle Charging due to Ion Attachment - Mallios, Sotirios A.; Papangelis, Georgios; Hloupis, George; Papaioannou, Athanasios; Daskalopoulou, Vasiliki; Amiridis, Vassilis (Frontiers in Earth Science, 2021)
The attachment of positive and negative ions to settling spherical dust particles is studied. A novel 1D numerical model has been developed to parameterize the charging process in the presence of a large-scale electric field. The model is able to self-consistently calculate the modification of atmospheric ion densities in the presence of the dust particles, and the consequent alteration of the atmospheric electrical conductivity and the large-scale electric field. Moreover, the model estimates the acquired electrical charge on the dust particles and calculates the electrical force that is applied on them. Using observed dust size distributions, we find that the particles can acquire electrical charge in the range of 1–1,000 elementary charges depending on their size and number density. The particles become mainly negatively charged, but under specific conditions giant mode particles (larger than 50 μm radius) can be positive. Moreover, the large-scale electric field can increase up to 20 times as much as the fair weather value. However, our approach shows that the resultant electrical force is not enough to significantly influence their gravitational settling, as the ratio between the electrical force magnitude and the gravity magnitude does not exceed the value of 0.01. This indicates that the process of ion attachment alone is not sufficient to create strong electrical effects for the modification of particle dynamics. Therefore, other processes, such as the triboelectric effect and updrafts, must be included in the model to fully represent the impact of electricity on particle dynamics.